Ultraviolet photochemistry of ethane: implications for the atmospheric chemistry of the gas giants. Issue 19 (6th May 2020) - Chang, Yao; Yang, Jiayue; Chen, Zhichao; Zhang, Zhiguo; Yu, Yong; Li, Qingming; He, Zhigang; Zhang, Weiqing; Wu, Guorong; Ingle, Rebecca A.; Bain, Matthew; Ashfold, Michael N. R.; et al.
Abstract : The vacuum ultraviolet photodissociation dynamics of ethane provide clues for modelling the atmospheric chemistry of the gas giants. Abstract : Chemical processing in the stratospheres of the gas giants is driven by incident vacuum ultraviolet (VUV) light. Ethane is an important constituent in the atmospheres of the gas giants in our solar system. The present work describes translational spectroscopy studies of the VUV photochemistry of ethane using tuneable radiation in the wavelength range 112 ≤ λ ≤ 126 nm from a free electron laser and event-triggered, fast-framing, multi-mass imaging detection methods. Contributions from at least five primary photofragmentation pathways yielding CH2, CH3 and/or H atom products are demonstrated and interpreted in terms of unimolecular decay following rapid non-adiabatic coupling to the ground state potential energy surface. These data serve to highlight parallels with methane photochemistry and limitations in contemporary models of the photoinduced stratospheric chemistry of the gas giants. The work identifies additional photochemical reactions that require incorporation into next generation extraterrestrial atmospheric chemistry models which should help rationalise hitherto unexplained aspects of the atmospheric ethane/acetylene ratios revealed by the Cassini–Huygens fly-by of Jupiter.